Transportation mode choice to campus study in the new normal era (case study: Al-Azhar University) - Nur Asiyah; Damanik, Syafrida; Ramadhan, Rizky (Jurnal VORTEKS, 2024)
This research aims (1) to find out the types of transportation modes used by students in the new normal era (2) to find out the factors that influence students in choosing transportation modes in the new normal era (3) to identify the characteristics of students in choosing transportation modes in the new normal era. new normal. The method used in this research is a quantitative method with a deductive approach because the researcher tests general problems based on testing a theory consisting of variables in choosing transportation modes. Conclusions from this research were obtained The coefficient of determination (R square) is 0.612, which means the influence of the independent variables (health/environment, cost/cheap, speed, address of origin, monthly transportation costs, monthly transportation money, security, comfort, travel time, convenience, availability, pocket money per month, gender, vehicle ownership, semester, driver's license ownership) of the dependent variable (mode type) is 61.2%, it is known that the calculated F value = 3.449 with a significance level of 0.001<0.05, so it can be concluded that these variables affect the choice of transportation mode for Al-Azhar University Medan students